2003
DOI: 10.1038/nature02208
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary conservation of biogenesis of β-barrel membrane proteins

Abstract: The outer membranes of mitochondria and chloroplasts are distinguished by the presence of beta-barrel membrane proteins. The outer membrane of Gram-negative bacteria also harbours beta-barrel proteins. In mitochondria these proteins fulfil a variety of functions such as transport of small molecules (porin/VDAC), translocation of proteins (Tom40) and regulation of mitochondrial morphology (Mdm10). These proteins are encoded by the nucleus, synthesized in the cytosol, targeted to mitochondria as chaperone-bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
444
2
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(464 citation statements)
references
References 29 publications
15
444
2
3
Order By: Relevance
“…60 Tob55/Sam50 channel is~7-8 nm large enough to accommodate the 16-22 β-strands of a β-barrel protein. 61 It is even speculated to work as an oligomer to facilitate the lateral release of the β-barrel protein being membrane-inserted, which in this context could increase its channel cutoff. 62,63 However, even as a monomer this channel is large enough to accommodate the 3.5x5 nm diameter of the GB ellipsoid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Tob55/Sam50 channel is~7-8 nm large enough to accommodate the 16-22 β-strands of a β-barrel protein. 61 It is even speculated to work as an oligomer to facilitate the lateral release of the β-barrel protein being membrane-inserted, which in this context could increase its channel cutoff. 62,63 However, even as a monomer this channel is large enough to accommodate the 3.5x5 nm diameter of the GB ellipsoid.…”
Section: Discussionmentioning
confidence: 99%
“…38 Interestingly, in agreement with our findings, it was previously reported that Tob55/Sam50 channel could have a role in apoptosis. 61,64 Tim22 and mtHsp70 are required for granzyme to cross the inner membrane. Tim22 is the core channel of the metabolite carrier translocase complex.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that Taz1 follows the same transport pathway as carrier proteins and ␤-barrel proteins across the outer membrane. However, although further transport of ␤-barrel proteins requires the SAM complex Kozjak et al, 2003;Paschen et al, 2003) Taz1 transport was independent of the SAM complex. Thus, import, fractionation, and analysis of the biogenesis support an outer membrane localization for Taz1.…”
Section: Taz1 and Respiratory Chain Complexesmentioning
confidence: 99%
“…To do this, we developed a BN-PAGE based assay to analyze assembly of newly imported subunits of complex IV into preexisting protein complexes. Similar import and assembly assays have successfully been used to assess outer membrane protein complex biogenesis (Krimmer et al, 2001;Model et al, 2001;Kozjak et al, 2003;Paschen et al, 2003;Wiedemann et al, 2003). Newly imported Cox5a assembled into the complex Figure 6.…”
Section: Taz1 and Respiratory Chain Complexesmentioning
confidence: 99%
“…13) and the chloroplast proteins Toc75-III and Toc75-V/Oep80 (14). Remarkably, all three are essential as mutations such as sam50 in yeast and toc75-III or toc75-V are lethal (15)(16)(17).…”
mentioning
confidence: 99%